Captain Underpants and the wrath of the wicked Wedgie Woman : the fifth epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 2001)
George and Harold's attempts to hypnotize their teacher results in the creation of the monstrous Wedgie Woman, who sets out to rule the world by getting rid of Captain Underpants.
4.3
3-6
3-6
School Library Journal
Kirkus Review
GN 640
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; Heroes -- Juvenile fiction; Monsters -- Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Heroes -- Fiction; Monsters -- Fiction; Captain Underpants (Fictional character) -- Fiction; Heroes and heroines -- Fiction; Monsters -- Fiction; School stories; Humorous fiction